Surviving cancer: The psychosocial outcomes of childhood cancer survivors and its correlates. (July 2016) - Castellano-Tejedor, Carmina; Pérez-Campdepadrós, Marta; Capdevila, Lluís; Blasco-Blasco, Tomás
This study assessed the psychosocial outcomes of adolescent cancer survivors and their relationship with personal and socio-familiar factors. Using a cross-sectional design, 41 survivors answered the four psychosocial dimensions of the KIDSCREEN-52 questionnaire and measures for social support and coping. Similarly, 41 parents answered coping and cancer-related distress measures. All psychosocial scores were within normative values (50 ± 10). Multiple linear regression analyses revealed four models with a range of explained variance between 9.4 percent and 31.9 percent that include the informative and emotional support, parental distress, and coping. This study contributes to the understanding of psychosocial outcomes of childhood cancer survivors and its correlates.